Pengaruh Skeptisisme Profesional, Due Professional Care, dan Tekanan Anggaran Waktu pada Kualitas Audit - Nikita Sari Wulan, Ni Putu Ayu; Budiartha, I Ketut (E-Jurnal Akuntansi, 2020)
Audit quality is one important aspect, because quality audit will reflect the actual conditions on the field. This research is to give the empirical fact of the effect of professional skepticism, due professional care, and time budget pressure on quality audit. The research is taking place at the BPK RI Perwakilan Provinsi Bali. The quantity of the sample is 52 auditors, using of non probability sampling method with the sampling sapurated technique. Questioner technique from the survey method used to collects the datas. Analisys technique that used in this research is multiple linear regression analisys technique. The result of the research showed that the professional skepticism and due professional care significantly give positive effects to the quality audit, meanwhile time  budget pressure significantly give negative effects to the quality audit. Keywords: Professional Skepticism; Due Professional Care; Time Budget Pressure; Quality Audit.